UJI EFEKTIVITAS EKSTRAK BIJI PICUNG (Pangium edule) SEBAGAI SENYAWA ANTIBAKTERI TERHADAP BAKTERI Staphylococcus aureus DAN Escherichia coli SECARA IN VITRO DENGAN METODE DIFUSI - Ganang Aji Handoko (2014)
Staphylococcus aureus is a bacterium that can cause disease in humans, such as skin infections, pneumonia, and food poisoning, as well as Escherichia coli can cause diarrhea, and urinary tract infections. Both of these bacteria are also resistant to some medicine. Indonesia has a diversity of medicinal plants. One of them is picung. Picung seeds extract contains tannin, cyanide acid, flavonoids, alkaloids, and saponins which act as antibacterial. The aim of this research is to determine the effectiveness of antibacterial picung seeds extract against S. aureus and E. coli. Used an experimental design with a diffusion method using Mueller Hinton Agar medium in order to see the inhibition zone around the paper disc.Picung seeds extracted by maceration using 96% ethanol. The results showed an average inhibition zone against S. aureus concentration of 25%, 50%, 75%, and 100% in a row are 1,37 ± 0,27 mm; 1,91 ± 0,40 mm; 3,54 ± 1,17 mm; and 5,47 ± 1,46 mm. While the E. coli concentration of 25%, 50%, 75%, and 100% in a row are 1,78 ± 0,42 mm; 2,23 ± 0,43 mm; 4,15 ± 0,51 mm; and 5,82 ± 1,04 mm. The conclusion is Picung seeds (Pangium edule) extract has effectiveness for inhibition activity against S. aureus and E. coli.